Determinants of Teacher Turnover in Private Schools of Mahalaxmi Municipality, Lalitpur - Makshindra Thapa; Deepa Bhujel (Journal of Development and Administrative Studies, 2025)
This study investigates the determinants of teacher turnover intention in Nepalese private schools, focusing on the relationship with supervisors, compensation, work conditions, job enrichment, and recognition. The research aimed to analyze how these variables relate teacher decisions to leave their organizations. Data were collected from 264 teachers working in private schools in Mahalaxmi municipality, Lalitpur through a structured questionnaire on a five-point Likert scale. Descriptive and correlational research designs were employed, and Pearson’s correlation analysis was used to assess the relationships among the variables. Results indicated that compensation and recognition significantly reduce turnover intention, highlighting their critical role in retention strategies. Interestingly, work conditions showed a positive and significant association, suggesting that better work environments may paradoxically increase turnover intent by encouraging teachers to seek better opportunities. Relationships with supervisors and job enrichment demonstrated no significant associations. The study offers theoretical insights into motivation and job satisfaction frameworks and practical recommendations for enhancing employee retention in private educational institutions.